2012
DOI: 10.2172/1051893
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Impurities in Module Packaging on Potential-Induced Degradation

Abstract: Chemical compounds were added into crystalline silicon cell mini modules, including in the encapsulant, interfaces, and glass, to determine their effect on potential-induced degradation (PID). Fe, either in the glass or at the glass/encapsulant interface, was found to be correlated with increased PID, but the difference in module power loss was not statistically significant compared to controls. Additions of Cu, Cr, Pb, Sn, Ag, and Na compounds to either the encapsulant or at the glass/encapsulant interface di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…If the modules/cells are not resistant to PID, the degradation mechanism can result in yield losses of 20 percent or more within a period of one year. According to recent publications, the PID shunting effect (PID-s), which decreases strongly the parallel resistance RP of the modules, is the most relevant type of PID [4,5]. However, it has also been shown that PID-s can influence the recombination behavior of the solar-cell [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…If the modules/cells are not resistant to PID, the degradation mechanism can result in yield losses of 20 percent or more within a period of one year. According to recent publications, the PID shunting effect (PID-s), which decreases strongly the parallel resistance RP of the modules, is the most relevant type of PID [4,5]. However, it has also been shown that PID-s can influence the recombination behavior of the solar-cell [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Sodium has also been found in high concentrations in stacking faults penetrating the junction . It has also been speculated that ions accelerated over an insulating dielectric or antireflective coating under an electric field may imbed in and damage the junction . Corona discharge over cells has been found to induce PID‐like junction failure .…”
Section: Introductionmentioning
confidence: 99%
“…Sodium has also been found in high concentrations in stacking faults penetrating the junction [5]. It has also been speculated that ions accelerated over an insulating dielectric or antireflective coating under an electric field may embed and damage the junction [6] in view that corona discharge over cells has been found to induce PID-like junction failure [7]. Considering that both reversible and irreversible components of junction failure are associated with system voltage stress [8], it is conceivable that multiple mechanisms are active.…”
Section: Introductionmentioning
confidence: 99%